Use of passive sensing to quantify adolescent mobile device usage: Feasibility, acceptability, and preliminary validation of the eMoodie application. Issue 1 (5th January 2021) - Domoff, Sarah E.; Banga, Claire Ann; Borgen, Aubrey L.; Foley, Ryan P.; Robinson, Chelsea; Avery, Katie; Gentile, Douglas A.
Abstract: Utilizing the built‐in features of smartphones, a novel app "eMoodie" (www.emoodie.com ) was developed which passively collects information on app and smartphone/tablet usage including duration and time of use. Youth in the US and UK participated in piloting and validating eMoodie. In the first study, we evaluated the feasibility and acceptability of eMoodie in a sample of 23 parent–child dyads ( N = 46), with children ages 10–12 years. Children downloaded eMoodie onto their device, which collected information on their screen time and app usage for seven consecutive days. Children responded to notifications via eMoodie to complete ecological momentary assessments (EMA) on wellbeing and digital media use. In the second study, caregiver‐child dyads participated ( N = 526) in a study conducted in Edinburgh, Scotland. Early adolescents (ages 11 to 14) participated in a remote study using eMoodie involving an EMA component, questionnaires, and passive sensing data collection over a 7‐day EMA study. To examine the preliminary validity of using eMoodie, we evaluated whether app‐enabled research may alter the behavior being studied. As youth are increasingly using mobile devices, capturing objective use and evaluating the correlates of such use on development grows ever more important. Remote data capture will be essential to continuing developmental research that cannot be facilitated in face‐to‐face settings due to the ongoing pandemic. As the first empirical investigation into the utility of an app that objectively measures adolescents' smartphone use, we summarize lessons learned in implementing this novel methodology and future directions for the measurement of mobile media.